P42 The relationship of home activity levels to psychological co-morbidity in COPD. (2nd December 2011) - Stuart, T; Rogers, C; Balanos, G; Wood, A M
Abstract : Background: Physical activity levels are often reduced in patients with COPD, but are partially amenable to intervention, predominantly by rehabilitation. Depression and anxiety are also commonly observed co-morbidities, which relate to outcomes such as mortality and admission rates.1 A recent meta-analysis of exercise as a treatment for depression suggested that it may improve depressive symptoms, 2 hence it is recommended by NICE guidance for mild depression. We hypothesised that less active COPD patients would also have higher rates of psychological co-morbidity. Methods: 59 consecutive COPD admissions or attendees to COPD clinic were recruited between January and March 2010, screened for anxiety and depression, and questioned regarding activity levels using the Modified Baecke Questionnaire (MBQ). Those who were already on treatment for anxiety or depression were excluded from further analysis (n=4). Home activity monitoring using the Actigraph was conducted in 20 patients and 6MWT distances recorded. Results: 38.2% of patients were anxious and 36.4% depressed, according to HADS. Both related strongly to exacerbation and admission rates over the preceding 12 months (p<0.01), and to QOL as measured by CAT (p<0.01). Perceived activity as measured by MBQ was lower in depressed patients (p=0.02); this remained significant after regression analysis, adjusting for exacerbations and FEV1 (p=0.03). However, actual activity from the Actigraph showed no relationship to either anxiety or depression (both p>0.38). Conclusions: Depressed patients perceive their symptoms to be more severe, and therefore their activity levels lower, than non-depressed patients. However, this did not translate into a difference in actual activity levels. Whether exercise programmes can impact on psychological co-morbidity in COPD requires further research.